2014
DOI: 10.1002/mnfr.201300758
|View full text |Cite
|
Sign up to set email alerts
|

Dietary deprivation of each essential amino acid induces differential systemic adaptive responses in mice

Abstract: Dietary deprivation of individual EAAs induced systemic adaptive responses that differed in magnitude and molecular machinery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…In growing pigs, the suppressive effect on growth after valine-or tryptophan-deficiency treatment is mainly associated with a reduction in feed intake (14)(15)(16)34) . Recent studies with mice have shown that dietary deficiency in isoleucine, valine and leucine causes the most dramatic decrease in feed intake (17) . In this study, we reported that the deficiency of valine and isoleucine in diet (NC group) for 4 weeks reduced the feed intake of piglets, which was restored to the level of the PC group after dietary supplementation with BCAA (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In growing pigs, the suppressive effect on growth after valine-or tryptophan-deficiency treatment is mainly associated with a reduction in feed intake (14)(15)(16)34) . Recent studies with mice have shown that dietary deficiency in isoleucine, valine and leucine causes the most dramatic decrease in feed intake (17) . In this study, we reported that the deficiency of valine and isoleucine in diet (NC group) for 4 weeks reduced the feed intake of piglets, which was restored to the level of the PC group after dietary supplementation with BCAA (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that branched-chain AA (BCAA), particularly valine and isoleucine, are the next-limiting AA for growth of piglets, and supplementation with these AA makes it possible to maintain growth performance of piglets fed reduced-protein diets (10,12,13) . Moreover, it has been demonstrated that dietary deficiency of AA causes a rapid decline in animal feed intake, which is particularly the case for BCAA in pigs (14)(15)(16) and mice (17) . In pigs, the suppressive effect of valine deficiency on feed intake is aggravated by an excess supply of leucine due to the shared enzymes in their catabolic pathways, which thereby increases the catabolism of valine (18) .…”
mentioning
confidence: 99%
“…For real-time reverse transcription PCR (RT-PCR), 2 μg total RNA was used to produce first-strand complementary DNA (cDNA) with a ReverTra Ace qPCR RT kit (Toyobo), and 10 ng cDNA from each sample was amplified via PCR using KOD SYBR qPCR Mix (Toyobo), primer sets (Supplementary Table S1), and a CFX96 Touch Real-Time PCR Detection System (Bio-Rad). The messenger RNA (mRNA) levels were quantified using the comparative CT method with hypoxanthine guanine phosphoribosyl transferase (Hprt, a housekeeping gene) levels for normalization [31].…”
Section: Microarray and Rt-pcrmentioning
confidence: 99%
“…1), particularly those under the control of the GCN2/eIF2a pathway, including SLC38A2 (SNAT2/System A) and the aforementioned CAT1 (Malmberg and Adams 2008;Fernandez et al 2002;Kamata et al 2014). However, chronic starvation of amino acids can also decrease the expression of these transporters in a tissue-specific manner (Kamata et al 2014), demonstrating complex regulation of these transporters.…”
Section: Extracellular Amino Acid Influxmentioning
confidence: 99%